Fertility induction in hypogonadotropic hypogonadal men. (9th October 2018) - Prior, Matthew; Stewart, Jane; McEleny, Kevin; Dwyer, Andrew A.; Quinton, Richard
Summary: Men with hypogonadotropic hypogonadism (HH) are typically azoospermic, and yet HH is one of the few treatable forms of male infertility. Sperm induction protocols using gonadotrophins aim to replicate the natural endocrine control of spermatogenesis. Previously virilised men with adult‐onset HH and normal testicular volume respond well to monotherapy in which human chorionic gonadotrophin (hCG) acts as a long‐acting LH‐analogue stimulating spermatogenesis. However, this approach is rarely successful for men with congenital HH (CHH) (eg, Kallmann syndrome), for whom combined gonadotrophin therapy (hCG + follicle‐stimulating hormone [FSH]) is an absolute requirement to maximise fertility potential. Key baseline predictors of successful spermatogenesis‐induction include prior spontaneous testicular development (ie, testicular volume [TV] > 4 mL), serum inhibin B (IB ) concentration >60 pg/mL and no history of maldescended testes (cryptorchidism).